2013
DOI: 10.1021/es304261s
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure is Associated with Negative Effects on Turtle Reproduction

Abstract: Mercury (Hg), a ubiquitous and highly toxic bioaccumulative contaminant, can maternally transfer and elicit deleterious effects on adult reproduction and offspring phenotype in fish, amphibians, and birds. However, the effects of Hg on reproduction remain largely unstudied in reptiles. We evaluated the consequences of maternally transferred Hg on a long-lived aquatic omnivore, the common snapping turtle (Chelydra serpentina). We collected eggs and tissues from gravid female turtles along a broad Hg contaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 38 publications
3
61
0
Order By: Relevance
“…The three eggs from each clutch were lyophilized and homogenized before being pooled as a composite sample. Samples were analyzed for total Hg at the College of William and Mary, Williamsburg, VA (see Hopkins et al (2013)) for additional information regarding Hg analysis). We tested multiple measures of performance of single hatchlings from 12 reference and 12 contaminated clutches.…”
Section: Turtle Collection and Husbandrymentioning
confidence: 99%
“…The three eggs from each clutch were lyophilized and homogenized before being pooled as a composite sample. Samples were analyzed for total Hg at the College of William and Mary, Williamsburg, VA (see Hopkins et al (2013)) for additional information regarding Hg analysis). We tested multiple measures of performance of single hatchlings from 12 reference and 12 contaminated clutches.…”
Section: Turtle Collection and Husbandrymentioning
confidence: 99%
“…In turtles, it was found that herbicides can affect organs and embryos, as well as mercury contamination (Hopkins et al, 2013, Zapata et al, 2014 and polychlorinated biphenyls (Matsumoto et al, 2014). Due to the strong anthropic pressure observed in the region, it is possible that Trachemys dorbigni has been mutating, and this can affect the permanence of this species in its natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies that examine species known to experience deleterious effects in response to Hg exposure [e.g. Bufo americanus, Thryothorus ludovicianus, Tachycineta bicolor and Chelydra serpentina (Bergeron et al, 2011;Hallinger et al, 2011;Jackson et al, 2011;Hopkins et al, 2013)] and that include larger sample sizes are needed to clarify the effects of Hg on wound healing and other aspects of immune function in wildlife.…”
Section: Discussionmentioning
confidence: 99%